Compressive strength of lithium disilicate inlay cementation on three different composite resins - Weng, Jui-Hung (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Ceramic restorations have been increasingly applied over recent years. But the performance of cement is still unknown after cementation. This study was aimed to compare the compressive strength and the performances of three different types of composite resin after lithium disilicate inlay cementation. MATERIALS AND METHODS: Twenty-four human maxillary premolars were embedded in resin blocks, finished a MOD inlay preparation and scanned with an extraoral scanner. Lithium disilicate ceramic inlays (IPS e.max, Ivoclar Vivadent, Liechtenstein) were fabricated according to the scanner's model. All the specimens were then etched, bonded, and cemented with three different composite resins. Right after 5000 thermal cyclings, the specimens were accepted compressive tests to evaluate the compressive strength and failure types. Moreover, the fracture fragments of the specimens were examined using scanning electron microscopy (SEM) to verify the fracture type. RESULTS: Dual-cured resin cement (Rely X Ultimate) showed the highest compressive strength (1002 ± 508 N), followed by the light-cured flowable resin (Z350 XT) (971 ± 209 N) and light-cured bulkfill (Filtek Bulkfill) resin (581 ± 191 N). Type IV (root fracture) failures in the dual-cured resin cement group was 25%, and light-cured flowable resin was 37.5%. But none of type IV fracture was found in the light-cured bulkfill flowable group. CONCLUSION: Dual-cured resin cement demonstrates the highest compressive strength after ceramic inlay cementation. Light-cured bulkfill resin shows the lowest compressive strength, but catastrophic failure is absent in this group.